STUDENTS’ VOICES ON MOBILE ASSISTED LANGUAGE LEARNING: PERCEPTIONS OF SPEAKING PRACTICE AND ANXIETY REDUCTION - Aulia Zahra, Jihan; Hamzah, Amir; Muljanto, Setia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores students’ perceptions of Duolingo, a Mobile Assisted Language Learning (MALL) platform, in supporting English speaking practice and reducing speaking anxiety. Using a qualitative exploratory design, data were collected through a screening questionnaire and semi-structured interviews with seven English Education students at Institut Pendidikan Indonesia Garut who had used Duolingo for at least three months. The questionnaire was organized into two categories: students’ perceptions of Duolingo for speaking practice (pronunciation, grammar, vocabulary, fluency) and the role of Duolingo in reducing speaking anxiety (accessibility, autonomous learning, immediate feedback, repeated exposure, and a low-pressure environment). Findings show that participants perceived Duolingo positively for developing speaking skills, with an overall mean of 4.41 (“Agree”); pronunciation and grammar improved the most, while fluency improved the least. Regarding anxiety, participants agreed that Duolingo helped reduce their speaking anxiety, with an overall mean of 4.36. Immediate, non-judgmental feedback (4.86) and a low-pressure, judgment-free environment (4.71) emerged as the most influential features in reducing communication apprehension, fear of negative evaluation, and test anxiety. One participant reported that fear of negative evaluation motivated rather than hindered her preparation, suggesting that anxiety does not always function as a debilitating factor. The study concludes that Duolingo serves as a safe space that bridges independent speaking practice and classroom performance, functioning as a complementary rather than a substitute tool for formal speaking instruction.